A three-dimensional and multi-source integrated technology system for controlling rural non-point source pollution in the Three Gorges Reservoir Area, China. (1st November 2020) - Zhong, Shouqin; Chen, Fangxin; Xie, Deti; Shao, Jingan; Yong, Yi; Zhang, Sheng; Zhang, Qingwen; Wei, Chaofu; Yang, Qingyuan; Ni, Jiupai
Abstract: Techniques for controlling rural non-point source pollution (RNSP) represent cleaner production techniques that can provide an effective guarantee for regional sustainable development. The majority of studies on RNSP control technologies are mainly aimed at handling only a single pollution source. However, such studies are difficult to perform in rural areas, which have dense populations, complex terrains and extreme climates, such as the Three Gorges Reservoir Area (TGRA), China. Therefore, this paper focuses on the application of the RNSP control technologies based on the following four aspects: crop planting, livestock production, domestic inputs and water-level-fluctuating (WLF) zone. Based on the unique topography, land features and planting patterns of the TGRA, a three-dimensional (3D) and multi-source integrated technology system for controlling RNSP was established according to the principle of source reduction, runoff regulation, and nitrogen (N) and phosphorus (P) loss control. From the results of the long-term observations, the risk of RNSP has been significantly reduced in the study area. The nutrient capacity of the soil increased by 9–15%, while the chemical fertilizer application reduced by 30–50%. The loss of sediment, N and P were reduced by 60–80%, 30–70% and 50–90% in the sloping land at the backslope, respectively, by 30–60%, 70–90%, and 70–90% in the paddy field at the footslope, respectively, and by 75–90%, 30–50%, 65–95% in the WLF zone, respectively. The average removal rates of COD, NH3 -N and TN in sewage in the residential area were higher than 82%, 87% and 63.3%, respectively. Overall, more than 90% of RNSP was reduced by using this 3D and multi-source technology system, and it can be widely promoted for controlling RNSP in similar ecological areas with support from local governments by implementing effective measures, such as strengthening environmental protection education and government subsidies. Graphical abstract: Image 1 Highlights: A multi-source integrated technology system was constructed to control RNSP in the TGRA. A 3D controlling mode was adopted to intercept RNSP based on the terrain of TGRA. More than 90% RNSP was reduced by this 3D and multi-source technology system. This technology system promoted the sustainable development of environment in the TGRA.